Understanding post-privatisation performance of statutory bodies subject to government shareholding: A suggested theoretical framework, for malaysian researchers - Philip Sinnadurai; S. Susela Devi (Journal of Risk and Financial Management, 2022)
The purpose of this concept paper is to suggest a theoretical framework for understanding the post-privatisation performance of statutory bodies, subject to government shareholding. We identify a suitable model, from the analytical economics literature. We argue that this model is a manifestation of agency theory. Our proposed framework for using this theory is replete with examples from Malaysia. We conclude that in Malaysia, the principal determinant of whether government subsidisation enhances or erodes shareholder wealth is the level of government shareholding. We also predict that in Malaysia, the relation between shareholder wealth and government shareholding follows an "inverted U" shape. However, the turning is likely to vary, cross-sectionally and temporally. We believe that the framework presented within this paper can be used to understand empirical results reported by other Malaysian studies into the shareholder wealth effects arising from economic policies featuring close co-operation between the public and private sectors.
Keywords: 650; analytical economics; government subsidisation; public policy; shareholder wealth